THERMAL IMAGING ACCURACY ON CLINICAL ACTIVITY SCORE (CAS) THYROID EYE DISEASE PATIENTS: Oral Presentation - Experimental Study - Ophthalmologist - MUHAMMAD REZA ARLAS; dr. Devi Azri Wahyuni, Sp.M, Sub.Sp NO, MARS (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Thyroid Eye Disease (TED) also known as Graves' ophthalmopathy, thyroid-associated orbitopathy, and other terms is an autoimmune inflammatory disorder with the most common extra-thyroid manifestations of Graves' Disease (GD). The disease phase is usually assessed clinically, by assessing the presence or absence of cardinal signs and symptoms of inflammation which are assessed in the form of a clinical activity score (CAS). In addition, the use of Thermal Imaging (IT) as a passive measurement technique that does not require contact with the patient (non-invasive and non- contact) and does not use ionizing radiation or contrast agents is another option. The use of TI in patients with TED still has minimal data and does not have more specific results. This study aims to determine the accuracy of TI and CAS images in TED patients. Methods : This study design is accuracy test at the Ophthalmology Polyclinic of RSUP Dr. Mohamad Hoesin Palembang in July 2021 until the sample is filled with 24 people. Thermal Imaging (TI) accuracy test was performed to establish active and inactive TED compared to CAS (Clinical Activity Score) in TED patients. Analysis of research results with SPSS version 22.0. Results : The result shown that the proportion of research subjects who were female was 17 people (70.8%) and male research subjects were 7 people (29.2%). At 7 locations the Thermal Imaging examination was found to have varying sensitivity Conclusion : Thermal Imaging can be used to help diagnose active and inactive TED.